Clinical and anamnestic differences between acute and chronic urticaria in children - R. M. Faizullina; Z. A. Shangareeva; A. V. Sannikova; V. V. Viktorov; S. M. Popova; L. M. Kabirova; A. R. Idrisova (Медицинский вестник Юга России, 2021)
Objective: to study clinical, anamnestic, and laboratory parameters in children with acute and chronic urticaria. Materials and methods: fifty-five children were examined who were admitted to the pediatric department and day-time inpatient facility of the State Children’s Clinical Hospital No. 17 in Ufa in 2019. Two groups were formed: 44 patients with acute urticaria (Group 1) and 11 patients with chronic urticaria (Group 2). For the correct analysis of the hemogram and immunogram, 2 subgroups of patients with acute urticaria were formed: Group 1a – 13 children under 5 years old and Group 1b – 31 children over 5 years old. Results: acute urticaria was typical for young children (Z cor. = -2.14665; p = 0.031822). In children with acute urticaria under five years of age, there was a correlation (p < 0.05) of age with low serum JgA levels (rs = 0.806380) and the incidence of gastropathology with JgM levels (rs = 0.872872); JgG (rs = 0.763763) and the number of blood leukocytes (rs = 0.692820). In children with acute urticaria over five years of age, a correlation was found between age and concomitant gastropathology (rs = 0.421569). Patients with chronic urticaria are characterized by eosinophilia (Z cor. = -2.96741; p = 0.003003) and a pathogenetically significant increase in the CEC level (Z cor. = 1.98537; p = 0.047104). Conclusion: the revealed differences should be taken into account during the examination and management of children with urticaria.